2010
DOI: 10.1038/npp.2010.34
|View full text |Cite|
|
Sign up to set email alerts
|

Paroxetine-Induced Increase in Activity of Locus Coeruleus Neurons in Adolescent Rats: Implication of a Countertherapeutic Effect of an Antidepressant

Abstract: Concern that antidepressant (AD) drugs, especially selective serotonin reuptake inhibitors and paroxetine (PAR) in particular, can increase suicidality during the early treatment of juvenile patients (children and adolescents) has created a dilemma for clinicians treating depressives. Though preclinical research cannot resolve controversy in this area, our present findings may provide insight into how AD drugs might, under certain conditions, exacerbate rather than ameliorate the depressive state. Both clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 57 publications
0
16
0
1
Order By: Relevance
“…TH). In contrast, West et al (2010) reported that paroxetine-induced increases of LC activity in adolescent rats (PN45) was restricted to acute exposure (2-4 days), but was more similar to adult exposure (decreased LC activity) after longer-term treatment (8-14 days). This increased activity complements our results but, with the apparent difference in chronic vs acute exposure in the above mentioned study, it is apparent that the identification of critical windows of antidepressant sensitivity on neurodevelopment needs to be investigated further.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…TH). In contrast, West et al (2010) reported that paroxetine-induced increases of LC activity in adolescent rats (PN45) was restricted to acute exposure (2-4 days), but was more similar to adult exposure (decreased LC activity) after longer-term treatment (8-14 days). This increased activity complements our results but, with the apparent difference in chronic vs acute exposure in the above mentioned study, it is apparent that the identification of critical windows of antidepressant sensitivity on neurodevelopment needs to be investigated further.…”
Section: Discussionmentioning
confidence: 90%
“…Increased LC firing when SSRIs were administered during adolescence (PN45) was interpreted as a possible explanation for the increased risk for suicide in younger populations taking SSRIs (West et al, 2010; Goodman et al, 2007). We extend these findings to earlier periods of neurodevelopment and suggest this earlier manipulation of the monoamine system may result in long lasting modifications of the NE-LC system in males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In adolescent rats, SSRIs early in treatment had the effect of increasing, rather than decreasing, LC activity and depression-like behavior. By contrast, tricyclics, which are not associated with increased risk of suicidality in adolescents, decreased LC activity in both adult and adolescent rats (West et al, 2010a; West et al, 2010b). …”
Section: Depressionmentioning
confidence: 92%
“…Cette augmentation de noradrénaline suggère une augmentation d'activité dans le LC et a été liée à des choix impulsifs (Eckhoff et al,, 2009) ainsi qu'à des changements comportementaux rapides en réponse à des challenges cognitifs, par la facilitation de la réorganisation dynamique des réseaux corticaux (Bouret et Sara, 2005). Cette hypothèse s'appuie aussi sur l'observation qu'une prise brève d'antidépresseur chez des jeunes rats augmente les décharges des neurones dans le LC, et est associé avec une péjoration de la dépression (West et al, 2010), suggérant par là que l'augmentation d'activité du LC puisse être associée aux effets secondaires du traitement antidépresseur sur l'humeur particulièrement chez les jeunes.…”
Section: Substrats Neurobiologiques Du Processus Suicidaireunclassified